Preparation and evaluation of 99mTc-labeled porphyrin complexes prepared using PNP and HYNIC cores: studying the effects of core selection on pharmacokinetics and tumor uptake in a mouse model. Issue 4 (21st March 2019) - Guleria, Mohini; Das, Tapas; Vats, Kusum; Amirdhanayagam, Jeyachitra; Mathur, Anupam; Sarma, Haladhar D.; Dash, Ashutosh
Abstract : Demonstration of the effect of using two different 99m Tc-cores for radiolabeling of the same ligand: differential in vivo outcome. Abstract : Porphyrins are tetrapyrrolic macrocyclic ligands known for their affinity towards neoplastic tissues and once radiolabeled with a suitable diagnostic radioisotope could potentially be used for the imaging of tumorous lesions. In the present study, an unsymmetrically substituted porphyrin derivative namely 5-( p -amino-propyloxyphenyl)-10, 15, 20-tris(carboxymethyleneoxyphenyl)-porphyrin was synthesized and modified further to enable radiolabeling with 99m Tc using two different 99m Tc-cores viz. 99m Tc-HYNIC (hydrazino nicotinic acid) and 99m Tc(N)PNP2 (PNP2 = bis-[(2-dimethylphosphino)ethyl]-methoxy-ethylamine) in order to study the effect of employing different 99m Tc-cores on tumor affinity and pharmacokinetic behavior of the resultant 99m Tc-labeled porphyrin complexes. 99m Tc–Porphyrin complexes were characterized by reversed phase HPLC studies and could be prepared with >95% radiochemical purity under optimized radiolabeling conditions. Both 99m Tc-complexes were found to be adequately stable in human blood serum till 3 h post-preparation. Bio-distribution studies, carried out in Swiss mice bearing fibrosarcoma tumors, revealed relatively higher tumor uptake for the 99m Tc-HYNIC–porphyrin complex (3.95 ± 1.42 and 3.28 ± 0.27% IA per g) compared to that exhibited by the 99m Tc(N)PNP-DTC–porphyrin complex (1.52 ± 0.53 and 1.56 ± 0.10% IA per g) at 1.5 and 3 h post-administration, although the former complex exhibited comparatively lower lipophilicity in the octanol–water system. Higher uptake and longer retention in the blood were observed for the 99m Tc-HYNIC–porphyrin complex (6.63 ± 0.75 and 4.36 ± 0.25% IA per g) compared to that exhibited by the 99m Tc(N)PNP-DTC–porphyrin complex (2.41 ± 0.54 and 2.30 ± 0.16% IA per g) at both 1.5 and 3 h post-administration. However, relatively lower liver uptake was observed for the former complex (19.26 ± 3.48 and 18.45 ± 1.05% IA per g) than that exhibited by the latter one (39.37 ± 3.88 and 34.15 ± 8.25% IA per g) at both 1.5 and 3 h post-administration. This study indicates that the in vivo behavior exhibited by the 99m Tc-labeled porphyrins not only depends on their lipophilicity/hydrophilicity but is also governed by the Tc-cores employed for radiolabeling.